The effectiveness of the existing law in protecting the personal information; a study on Mykad / Azreen Zairina Mohd Amin Zainoorin …[et al.] - Mohd Amin Zainoorin, Azreen Zairina; Mohd Yusop, Mohd Yuhelmy; Paul, Sue Rachelle (Faculty of Law, 2009)
Personal data is an asset to an individual and is at the stake of being misuse by other person especially on personal information that is stored in Mykad. It is clear that this personal information need some kind of protection from being misuse. The most effective protection commonly is the legal protection. Unfortunately, this concept is new to Malaysian and currently, there's no direct and effective laws governing this matter. "The first data protection law is said to have been enacted in the German state of Hesse in 1970 although Sweden was probably the first country to enact a national data protection law in 1973".1 In Malaysia, the closest that we can get is the Personal Data Protection Bill that was brought forward in 2001. However, the bill is not yet being tabled until today. This research paper is examining the effectiveness of existing laws in Malaysia in governing the protection on personal data in Mykad. The functions and features of Mykad would be examined in this research. There are quite a number of existing laws that indirectly protects the personal information stored in Mykad; however these laws are not specifically governing the personal information stored in Mykad. This research paper would examine critically the existing laws and examine the effectiveness of it on governing the personal information stored in Mykad. The proposed Personal Data Protection Bill will also be analyzed in this research. This research hopefully would show the importance of having specific laws governing this matter and to speed up the enforcement of the long awaited Personal Data Protection Law.